CHARACTERISTICS OF SOCIAL AND SPIRITUAL ASPECTS SPECIFIC TO RADICAL PERSONS APPEARING IN THE LIFE OF HUMANITY - Khalilov Jamoliddin Sadikovich (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the socio-spiritual aspects of radical individuals in human life. The article also talks about the manifestations of the socio-spiritual aspects characteristic of radical individuals in the modernizing Uzbekistan.